Soil Fungal Community Structure in Boreal Pine Forests: From Southern to Subarctic Areas of Finland - Qu, Zhao-Lei; Santalahti, Minna; Köster, Kajar; Berninger, Frank; Pumpanen, Jukka; Heinonsalo, Jussi; Sun, Hui (Frontiers in Microbiology, 2021)
The boreal forest environment plays an important role in the global C cycle due to its high carbon storage capacity. However, relatively little is known about the forest fungal community at a regional scale in boreal forests. In the present study, we have re-analyzed the data from our previous studies and highlighted the core fungal community composition and potential functional groups in three forests dominated by Scots pine (Pinus sylvestris L.) in Finland, and identified the fungal generalists that appear across geographic locations despite differences in local conditions. The three forests represent subarctic, northern and southern boreal forest, and are all in an un-managed state without human interference or management. The subarctic and northern areas are subject to reindeer grazing. The results showed that the three locations formed distinct fungal community structures (P < 0.05). Compared to the two northern locations, the southern boreal forest harbored a greater abundance of Zygomycota, Lactarius, Mortierella Umbelopsis, and Tylospora, in which aspect there were no differences between the two northern forests. Cortinarius, Piloderma, and Suillus were the core fungal genera in the boreal Scots pine forest. Functionally, the southern boreal forest harbored a greater abundance of saprotroph, endophytes and fungal parasite-lichen, whereas a greater abundance of ectomycorrhizal fungi was observed in the northern boreal forests. Moreover, the pathotroph and wood saprotrophs were commonly present in these three regions. The three locations formed two distinct fungal community functional structures, by which the southern forest was clearly separated from the two northern forests, suggesting a distance–decay relationship via geographic location. This study provides useful information for better understanding the common fungal communities and functions in boreal forests in different geographical locations.